Effect of altering ruminal pH by dietary buffer supplementation on methane emissions from sheep fed forage rape. (18th May 2020) - Sun, X. Z.; Harland, R.; Pacheco, D.
Abstract : Low methane (CH4 ) emissions from sheep fed forage rape ( Brassica napus ) might be related to low ruminal pH value. In this study, sodium carbonate (Na2 CO3 : SC ) was supplemented to the diet to alter ruminal pH for evaluation of its role in CH4 emissions from sheep fed forage rape. Fourteen intact and eight fistulated Romney sheep were adapted to forage rape over 32 days and then randomly allocated to one of two groups: diets supplemented with SC or not (control). Methane emissions were measured from intact sheep in seven experimental periods. In parallel, ruminal pH and fermentation characteristics were assessed using the fistulated sheep. In the first (P01) and the second (P02) periods, none of the sheep received SC to examine the baseline CH4 emissions. The P01 period was used as a covariate for analysis of gas emission measurements in subsequent measurement periods. Sodium carbonate was offered at 5% of the forage DM in P03 and P04, increased to 8% in P05 and P06 to assess the effect of pH increase on CH4 emissions and stopped in P07 to assess if the CH4 emissions reverted to values similar to those measured before the supplementation started. Methane yield (g/kg forage DM intake) was similar for the sheep in both groups during P02 and P03, but sheep supplemented with SC in the diet emitted 36%, 49% and 30% more CH4 per unit of forage DM intake than those in the control group during P04, P05 and P06, respectively. Emissions returned to similar levels when SC supplementation was ceased in P07. Ruminal pH was 0.412 to 0.565 units higher in SC supplemented sheep than for the control group during the SC treatment periods. Based on the lack of an immediate response in CH4 emissions to the supplementation of SC in P03, the positive responses in P04 to P06 and the rapid disappearance of the response after supplementation with SC stopped in P07, we propose a new hypothesis that ruminal pH effects on CH4 emissions are possibly through medium-term changes in microbial and methanogenic communities in the rumen, rather than a direct, short-term impact on methanogens per se . In conclusion, SC supplemented to the forage rape diet of sheep increased rumen pH, leading to an increase in CH4 emissions. Low ruminal pH in sheep fed forage rape explains, at least partially, the reported low CH4 emissions from sheep fed with this forage crop.